(untitled) (Basel Institute on Governance Working Papers, 2019)
This Working Paper aims to contribute to the international policy dialogue on the link between asset recovery and countries’ pursuit of the Sustainable Development Goals. It contends that supporting countries in recovering stolen assets and promoting sustainable development are mutually reinforcing. It also aims to correct the false reputation of asset recovery as a very technical legalistic field of development cooperation, and to generate broader understanding of the far-reaching role that asset recovery can play to foster development. The paper argues that helping countries recover stolen assets, anchored in target 16.4 of the SDGs, can mobilise important resources to finance development or poverty reduction efforts. In addition, it explores how asset recovery plays a critical role in strengthening some of the key foundations of sustainable development, such as the rule of law and strong, transparent and accountable institutions. Combining “hard assets” in terms of actual assets recovered and the “soft assets” that are needed to do so effectively, ranging from the capacity of law enforcement institutions to the political will to fight criminal networks, provides a powerful foundation for sustainable development.